1978
DOI: 10.1126/science.635592
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Functions for Perceived and Remembered Size

Abstract: Separate groups of people estimated the sizes of perceived or of remembered objects. In three independent experiments, both sets of data were well fit by power functions, and the exponent was reliably smaller by remembered than for perceived size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
76
2
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 11 publications
8
76
2
2
Order By: Relevance
“…This was not the case for any other estimation. Findings from the perceptual literature support the notion that size judgments differ for perceived and remembered size for the same object (Moyer, Bradley, Sorensen, Whiting, & Mansfield, 1978). However, the difference found in the Moyer et al study occurred in the opposite direction to that found in the current study, namely, that judgments made from memory tend to be larger than those made from perception.…”
Section: Discussionsupporting
confidence: 64%
“…This was not the case for any other estimation. Findings from the perceptual literature support the notion that size judgments differ for perceived and remembered size for the same object (Moyer, Bradley, Sorensen, Whiting, & Mansfield, 1978). However, the difference found in the Moyer et al study occurred in the opposite direction to that found in the current study, namely, that judgments made from memory tend to be larger than those made from perception.…”
Section: Discussionsupporting
confidence: 64%
“…In summary, there is a great deal of evidence that our memory for the magnitude of an instance is frequently less extreme than the original magnitude of the instance (Huttenlocher et al, 1991;Kerst & Howard, 1978;Moyer et al, 1978). The category adjustment model proposes that this assimilation reflects the use of estimation procedures that maximize the accuracy of estimates through prior probabilities established by category membership.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the psychophysical function derived from magnitude estimates of remembered stimuli is frequently flatter than the corresponding psychophysical function for estimates based on direct perception (Kerst & Howard, 1978;Moyer, Bradley, Sorensen, Whiting, & Mansfield, 1978). Similarly, in successive comparative judgment tasks, participants typically overestimate the magnitude of a low-magnitude stimulus relative to that of a second stimulus (i.e., a positive time-order error) but underestimate the magnitude of a high-magnitude stimulus relative to that of a second stimulus (i.e., a negative timeorder error) (Hollingworth, 1910).…”
mentioning
confidence: 99%
“…Memory researchers have long pursued another relation-that between remembered attributes of a stimulus (including its mere appearance in the past) and its objectively verifiable properties. Despite the obvious similarity in goals, the routine of memory psychophysics, in which the rigorous quantitative techniques of perceptual psychophysics are applied to remembered stimuli, has been a fairly recent development (Algom, 1992a(Algom, , 1992bAlgom & Cain, 1991a, 1991bAlgom & Marks, 1989;Algom, Wolf, & Bergman, 1985;Kerst & Howard, 1978;Moyer, Bradley, Sorensen, Whiting, & Mansfield, 1978;Moyer, Sklarew, & Whiting, 1982;Wolf & Algom, 1987). Typical procedures of memory psychophysics involve separate examinations of the relations between stimulus magnitude and perceptual judgments (resulting in a perceptual psychophysical function), and between stimulus magnitude and memory-based magnitude judgments (resulting in a memory psychophysical function).…”
mentioning
confidence: 99%